Distinct aging profiles of CD8+ T cells in blood versus gastrointestinal mucosal compartments - Dock, Jeffrey; Ramirez, Christina M.; Hultin, Lance; Hausner, Mary Ann; Hultin, Patricia; Elliott, Julie; Yang, Otto O.; Anton, Peter A.; Jamieson, Beth D.; Effros, Rita B. (PloS one, 2017)
A hallmark of human immunosenescence is the accumulation of late-differentiated memory CD8+ T cells with features of replicative senescence, such as inability to proliferate, absence of CD28 expression, shortened telomeres, loss of telomerase activity, enhanced activation, and increased secretion of inflammatory cytokines. Importantly, oligoclonal expansions of these cells are associated with increased morbidity and mortality risk in elderly humans. Currently, most information on the adaptive immune system is derived from studies using peripheral blood, which contains approximately only 2% of total body lymphocytes. However, most lymphocytes reside in tissues. It is not clear how representative blood changes are of the total immune status. This is especially relevant with regard to the human gastrointestinal tract (GALT), a major reservoir of total body lymphocytes (approximately 60%) and an anatomical region of high antigenic exposure. To assess how peripheral blood T cells relate to those in other locations, we compare CD8+ T cells from peripheral blood and the GALT, specifically rectosigmoid colon, in young/middle age, healthy donors, focusing on phenotypic and functional alterations previously linked to senescence in peripheral blood. Overall, our results indicate that gut CD8+ T cells show profiles suggestive of greater differentiation and activation than those in peripheral blood. Specifically, compared to blood from the same individual, the gut contains significantly greater proportions of CD8+ T cells that are CD45RA- (memory), CD28-, CD45RA-CD28+ (early memory), CD45RA-CD28- (late memory), CD25-, HLA-DR+CD38+ (activated) and Ki-67+ (proliferating); ex vivo CD3+ telomerase activity levels are greater in the gut as well. However, gut CD8+ T cells may not necessarily be more senescent, since they expressed significantly lower levels of CD57 and PD-1 on CD45RO+ memory cells, and had in vitro proliferative dynamics similar to that of blood cells. Compartment-specific age-effects in this cohort were evident as well. Blood cells showed a significant increase with age in proportion of HLA-DR+38+, Ki-67+ and CD25+ CD8+ T cells; and an increase in total CD3+ ex-vivo telomerase activity that approached significance. By contrast, the only age-effect seen in the gut was a significant increase in CD45RA- (memory) and concurrent decrease in CD45RA+CD28+ (naïve) CD8+ T cells. Overall, these results indicate dynamics of peripheral blood immune senescence may not hold true in the gut mucosa, underscoring the importance for further study of this immunologically important tissue in evaluating the human immune system, especially in the context of chronic disease and aging.